Characterizing and Commissioning the Sutherland High-Speed Optical Cameras (SHOC) - Coppejans, R.; Gulbis, A. A. S.; Kotze, M. M.; Coppejans, D. L.; Worters, H. L.; Woudt, P. A.; Whittal, H.; Cloete, J.; Fourie, P. (Publications of the Astronomical Society of the Pacific, 2013)
ABSTRACT Two identical new instruments, the Sutherland High-speed Optical Cameras (SHOC), have been developed for use on the South African Astronomical Observatory's (SAAO) 1.9, 1.0 and 0.75 m telescopes at Sutherland. The SHOC systems are fast-frame-rate, accurately-timed, high-quality, visible-wavelength imagers. Each system consists of a camera, global positioning system (GPS), control computer and peripherals. The primary component is an Andor iXon X3 888 UVB camera, utilizing a 1024 × 1024 pixel, frame-transfer, thermoelectrically-cooled, back-illuminated CCD. One of SHOC's most important features is that it can achieve frame rates of between 1 and 20 frames/s during normal operation (dependent on binning and subframing) with microsecond timing accuracy on each frame (achieved using frame-by-frame GPS triggering). Frame rates can be increased further, and fainter targets observed, by making use of SHOC's electron-multiplying (EM) modes. SHOC is therefore ideally suited to time domain astronomy where high frame rates and extremely accurate timing are critical. Here, we present details of the instrument components, characteristics measured during commissioning, science demonstrations, and development plans. Attention is specifically given to exploration of the signal-to-noise (S/N) parameter space as a function of EM and conventional modes. These results enable observers to optimize instrumental settings for their observations and clearly demonstrate the advantages and potential pitfalls of the EM modes.